Policing and social identity: procedural justice, inclusion and cooperation between police and public - Bradford, B (2014)
Accounts of the social meaning of policing and of the relationship between police and citizen converge on the idea that police behaviour carries important identity-relevant information. Opinions of and ideas about the police are implicated in the formation of social identities that relate to the social groups it represents - nation, state and community. Procedural justice theory suggests that judgements about the fairness of the police will be the most important factor in such processes. Fairness promotes a sense of inclusion and value, while unfairness communicates denigration and exclusion. Furthermore, positive social identities in relation to the police should on this account promote cooperation with it. This article presents an empirical test of these ideas in the context of the British policing. Data from a survey of young Londoners are used to show that perceptions of police fairness are indeed associated with social identity, and in turn social identity can be linked to cooperation. Yet these relationships were much stronger among those with multiple national identities. Police behaviour appeared more identity relevant for people who felt that they were citizens of a non-UK country, but for those who identified only as British there was a weaker link between procedural fairness and social identity, and here legitimacy judgements were the main 'drivers' of cooperation. Theoretical and policy implications are discussed. © 2012 © 2012 Taylor and Francis.